A new species of Eriogonum (Polygonaceae) from the Cape region of the Baja California Peninsula, Mexico - José Luis León-de la Luz; Jon Paul Rebman; Alfonso Medel-Narváez (Revista Mexicana de Biodiversidad)
We describe and illustrate Eriogonum  calaverense, a new species of Polygonaceae from the southern tip of the Baja California peninsula, Mexico. It is known only from the granitic rock crevices of Cerro de la Calavera, and others in the vicinity, in the southern Cape region mountains. This species is characterized by its suffrutescent habit, as well as by its densely tomentose indumentum, which on its leaves is manifested by different color shades on the upper and lower sides. We present a detailed botanical description, illustrations, and photographs of this new taxon. Since this species seems to be linked to special edaphic conditions, we provide some locations where it might also be found with additional field exploration. The exact taxonomic placement of this new taxon within the genus Eriogonum is still in question and future cytogenetic and molecular data might help to address this problem.